Direct observation of temperature-driven magnetic symmetry transitions by vectorial resolved MOKE magnetometry. (31st August 2017) - Luis F Cuñado, Jose; Pedrosa, Javier; Ajejas, Fernando; Perna, Paolo; Miranda, Rodolfo; Camarero, Julio
Abstract: Angle- and temperature-dependent vectorial magnetometry measurements are necessary to disentangle the effective magnetic symmetry in magnetic nanostructures. Here we present a detailed study on an Fe(1 0 0) thin film system with competing collinear biaxial (four-fold symmetry) and uniaxial (two-fold) magnetic anisotropies, carried out with our recently developed full angular/broad temperature range/vectorial-resolved magneto-optical Kerr effect magnetometer, named TRISTAN. The data give direct views on the angular and temperature dependence of the magnetization reversal pathways, from which characteristic axes, remanences, critical fields, domain wall types, and effective magnetic symmetry are obtained. In particular, although the remanence shows four-fold angular symmetry for all investigated temperatures (15 K–400 K), the critical fields show strong temperature and angular dependencies and the reversal mechanism changes for specific angles at a given (angle-dependent) critical temperature, showing signatures of an additional collinear two-fold symmetry. This symmetry-breaking is more relevant as temperature increases to room temperature. It originates from the competition between two anisotropy contributions with different symmetry and temperature evolution. The results highlight the importance of combining temperature and angular studies, and the need to look at different magnetic parameters to unravel the underlying magnetic symmetries and temperature evolutions of the symmetry-breaking effects in magnetic nanostructures.